Reading Techniques - María Emilia Acosta; Juan Carlos Castillo (Asociación Colombiana de Profesores de Ingles, 2016)
Everyone reads with some kind of purpose in mind. For instance, to keep up with the news, to obtain specific information or simply for pleasure. Effective reading means being able to read accurately and efficiently, understanding as much of a text as one needs in order to achieve one's purpose.